2008
DOI: 10.7557/23.5970
|View full text |Cite
|
Sign up to set email alerts
|

Real Boys Carry Girly Epics: Normalising Gender Bending in Online Games

Abstract: Players in online games frequently choose the opposite gender when they select an avatar. Previously, this has been attributed to a player's unconscious sexual anxieties and the need to experiment through the anonymous location of the avatar. However, this paper argues that the development of choice in games, where players have frequently selected the female form for ludic reasons, means that this choice has become normalised through a historical process. The avatar is frequently considered as a tool, with gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…For example, Ducheneaut et al (2006) found that in massively multiplayer online games, “male players who play Priests are more likely to gender-bend than those who play Warriors… thus, real world stereotypes come to shape the demographics of fantasy worlds” (p. 296). In general, male players in online games make aesthetic, strategic, pragmatic, and experimental choices in terms of “bending” gender (Martey et al, 2014; MacCallum-Stewart, 2008). In terms of race, games also “provide their primarily White creators and players the opportunity to become the other” (Leonard, 2006, p. 86) or to fill in the perceived blankness of their whiteness.…”
Section: Self and Subjectivity In The Contexts Of Power Imbalancementioning
confidence: 99%
See 4 more Smart Citations
“…For example, Ducheneaut et al (2006) found that in massively multiplayer online games, “male players who play Priests are more likely to gender-bend than those who play Warriors… thus, real world stereotypes come to shape the demographics of fantasy worlds” (p. 296). In general, male players in online games make aesthetic, strategic, pragmatic, and experimental choices in terms of “bending” gender (Martey et al, 2014; MacCallum-Stewart, 2008). In terms of race, games also “provide their primarily White creators and players the opportunity to become the other” (Leonard, 2006, p. 86) or to fill in the perceived blankness of their whiteness.…”
Section: Self and Subjectivity In The Contexts Of Power Imbalancementioning
confidence: 99%
“…Perceived defaultness of the White male identity (Zarate & Smith, 1990) implies that race is only recognized when it is non-White and when sex is only female (Stroessner, 1996). Thus, this blankness of the White male identity sometimes fosters members of the dominant group to objectify the identities of the others to fill their nominal subjectivities with it (MacCallum-Stewart, 2008; Nakamura, 2002). In contrast, members of marginalized groups face dissimilar circumstances of their choice.…”
Section: Self and Subjectivity In The Contexts Of Power Imbalancementioning
confidence: 99%
See 3 more Smart Citations